Musyarakah Financing Risk Management at Bank Syariah Indonesia - Muhammad Nasri Katman; Muh. Furqan Arajab; Idris Parakkasi (Universitas Islam Negeri Alauddin Makassar, 2022)
This study discusses the risk management of musyarakah contract financing at Indonesian Sharia Banks. The purpose of this study is to find out how the implementation of musyarakah financing risk management is carried out by BSI. The research approach used is a qualitative approach, with a qualitative descriptive method. The data sources used in this study are primary data obtained from the field through the process of collecting data using observation, interview and documentation methods and secondary data in the form of literature such as books, scientific journals and previous research to serve as reference material and also considerations in the preparation of this study. . The data analysis technique used is the method of data collection, data reduction, data presentation and data validity test. The results of this study indicate that Bank Syariah Indonesia has implemented a risk management process starting from identifying risks and taking preventive actions as early as possible such as submitting document requirements, examining financial reports and customer backgrounds to prevent these risks from occurring in the future, carrying out supervision in the activity reporting mechanism. customer business that is carried out every month as well as the restructuring process for customer financing that is experiencing problems, up to the mechanism for the final stage of financing settlement which must be clear and communicative to avoid misinformation that might occur.